Poverty, partiality, and the purchase of expensive education. (February 2017) - Freiman, Christopher
Prioritarianism doesn't value equality as such – any reason to equalize is due to the benefits for the worse off. But some argue that prioritarianism and egalitarianism coincide in their implications for the distribution of education: Equalizing educational opportunities improves the socioeconomic opportunities of the worse off. More specifically, a system that prohibits parents from making differential private educational expenditures would result in greater gains to the worse off than a system that permits these expenditures, all else equal. This article argues that prioritarianism opposes a cap on educational expenditures. The argument, in brief, is that an equalized provision of schooling does a worse job of channeling the partiality of rich families in ways that produce positive spillover for poorer children. My challenge to the prioritarian case for educational equality is an internal one: the very concerns about parental partiality that underlie prioritarian objections to uncapped educational expenditures apply with even greater force to a system that caps educational expenditures.